Peningkatan Produktivitas Usaha Kecil Menengah Kerupuk Udang Melalui Perancangan Pengeringan Dan Pengemasan - Yudha Prasetyawan; Moses L. Singgih; Esty Putrianingsih; Muhammad Ziyad (Jurnal METRIS, 2014)
The purpose of this research is to make a prototype for shrimp crackers process in the small industries. Thereare some processes to make shrimp crackers but the critical process is drying crackers. In fact, shrimpcrackers were usually drying under sunheat. Drying shrimp crackers process needs long time, not hiegenis,and unpredictable weather. This machine was designed to dry shrimp crackers easier, faster, and hiegenis.Prototype can dry shrimp crackers indoor. Otomation applied for drying and packing system to keepproduction rate. This system can increase production rate until 23%.